1982
DOI: 10.1177/0730888482009001003
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Technology on Alienation from Work

Abstract: This article presents new evidence on the effect of technology on alienation from work that is pertinent to Blauner's inverted U-curve hypothesis. One data set permits comparative analysis at the organizational level and addresses a gap in the literature on worker alienation because most research uses individual level data grouped by industrial categories. This organizational level approach is applied to individual level data on retrained union printers to analyze the impact of automation on the work of skille… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1983
1983
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…This almost purposeful misreading of the data must be tracked to ideological bias (Hamilton and Wright, 1982). Hatred of machines and bureaucracy leads many sociologists to attribute their feelings to the working class (Roberts, 1978), despite evidence that most workers like their machines and are not disturbed by working in bureaucracies (Mueller et al, 1969;Form, 1976a;Form and McMillen, 1983;Hull, Friedman, and Rogers, 1982). Professors probably underestimate the complexity of low skill jobs and workers' ingenuity in making them satisfying and/or bearable (Kusterer, 1978).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This almost purposeful misreading of the data must be tracked to ideological bias (Hamilton and Wright, 1982). Hatred of machines and bureaucracy leads many sociologists to attribute their feelings to the working class (Roberts, 1978), despite evidence that most workers like their machines and are not disturbed by working in bureaucracies (Mueller et al, 1969;Form, 1976a;Form and McMillen, 1983;Hull, Friedman, and Rogers, 1982). Professors probably underestimate the complexity of low skill jobs and workers' ingenuity in making them satisfying and/or bearable (Kusterer, 1978).…”
Section: Discussionmentioning
confidence: 95%
“…But even if technological explanations were accepted, most studies confirm Blauner's ( 1964) thesis that alienation is lower among workers in automated industries than in mechanical industries. Assuming that automation will increase, we may infer that work alienation will decrease (Hull, Friedman, and Rogers, 1982); however, no longitudinal research dealing with this question exists.…”
Section: Is Work Discontent Increasing?mentioning
confidence: 95%
“…For example, Wallace and Kalleberg's (1982) study documented an apparent sizable downgrading in skill levels of printing occupations. Yet, the study by Hull, Friedman, and Rodgers (1982) showed a small group of retrained printers from three large New York City newspapers enjoyed expanded, more intellectually demanding printing jobs after the technological change. Why did their experience differ so radically from the total group of printers?…”
Section: Summary Of Case Study Evidencementioning
confidence: 95%
“…Second, the case for more postsecondary general and vocational education comes from studies that show educated workers are better able to adapt to technological change and are less likely to experience the adverse consequences of technological change (for examples, see Hull et al, 1982;Jaffe & Froomkin, 1968;Mueller et al, 1969). In policy terms, this means more schooling for the lowest one-third or onehalf of persons in the schooling distribution versus more schooling for the top half, which might have the opposite effect of increasing educational inequality.…”
Section: General and Specific Skillsmentioning
confidence: 98%
“…On the other hand, Blauner (1964) proposed an empirical operationalization of Marx's concept of alienation into four dimensions: powerlessness, meaninglessness, social alienation and selfestrangement. This analysis, although open to criticism (Edgell 2006: 36), initiated a subjectivist tradition of studying intrinsic job quality which has been applied to different countries and work environments (see, for example, Shepard 1977;Hull et al 1982;Vallas 1988).…”
Section: Theoretical Background: Approaches To Measuring Job Qualitymentioning
confidence: 99%